ChemInform Abstract: Regioselective Tandem N‐Alkylation/C‐Acylation of β, γ‐Alkynyl α‐Imino Esters. Issue 1 (7th January 2014) - Mizota, Isao; Matsuda, Yuri; Kamimura, Satoshi; Tanaka, Hirotaka; Shimizu, Makoto
Abstract N‐addition to α‐imino esters followed by acylation provides alkynyl amino esters or allenoates in a regioselective tandem process.